Bodily Reactions to Emotional Words Referring to Own versus Other People’s Emotions - Weis, Patrick P.; Herbert, Cornelia (Frontiers in Psychology, 2017)
According to embodiment theories, language and emotion affect each other. In line with this, several previous studies investigated changes in bodily responses including facial expressions, heart rate or skin conductance during affective evaluation of emotional words and sentences. This study investigates the embodiment of emotional word processing from a social perspective by experimentally manipulating the emotional valence of a word and its personal reference. Stimuli consisted of pronoun-noun pairs, i.e., positive, negative, and neutral nouns paired with possessive pronouns of the first or the third person (“my,” “his”) or the non-referential negation term (“no”) as controls. Participants had to quickly evaluate the word pairs by key presses as either positive, negative, or neutral, depending on the subjective feelings they elicit. Hereafter, they elaborated the intensity of the feeling on a non-verbal scale from 1 (very unpleasant) to 9 (very pleasant). Facial expressions (M. Zygomaticus, M. Corrugator), heart rate, and, for exploratory purposes, skin conductance were recorded continuously during the spontaneous and elaborate evaluation tasks. Positive pronoun-noun phrases were responded to the quickest and judged more often as positive when they were self-related, i.e., related to the reader’s self (e.g., “my happiness,” “my joy”) than when related to the self of a virtual other (e.g., “his happiness,” “his joy”), suggesting a self-positivity bias in the emotional evaluation of word stimuli. Physiologically, evaluation of emotional, unlike neutral pronoun-noun pairs initially elicited an increase in mean heart rate irrespective of stimulus reference. Changes in facial muscle activity, M. Zygomaticus in particular, were most pronounced during spontaneous evaluation of positive other-related pronoun-noun phrases in line with theoretical assumptions that facial expressions are socially embedded even in situation where no real communication partner is present. Taken together, the present results confirm and extend the embodiment hypothesis of language by showing that bodily signals can be differently pronounced during emotional evaluation of self- and other-related emotional words.